The expression status of CD133 is associated with the pattern and timing of primary glioblastoma recurrence - Shibahara, Ichiyo (Oxford University Press, 2013)
BACKGROUND: Glioblastoma carries a poor prognosis primarily because of its high rate of recurrence. The ability to predict the recurrence pattern and timing would be highly useful for determining effective treatment strategies. We examined the correlation between prognostic factors and the pattern of recurrence in patients with primary glioblastoma. In particular, we examined whether there was a correlation between the expression of CD133 and glioblastoma recurrence. METHODS: We retrospectively analyzed 112 patients with primary glioblastoma. The timing and pattern (local or distant) of the initial recurrence were obtained from medical records. To identify factors predictive of recurrence, we examined CD133 expression by Western blots and immunohistochemistry, clinical (age, sex, KPS, Ki67 labeling index, surgery, ventricular entry) and genetic (IDH1, 7p, 9p, 10q, MGMT) factors. RESULTS: Of the 112 patients, 99 suffered recurrence. The first recurrence was local in 77 patients and distant in 22 patients. Among the factors to predict the pattern of recurrence, CD133 expression was significantly higher in distant than in local recurrence. Of the factors to predict the timing of recurrence, high CD133 expression was associated with shorter time to distant recurrence in both univariate and multivariate analyses (P = .0011 and P = .038, respectively). CONCLUSIONS: The expression of CD133 may be a predictor of the pattern and timing of recurrence of primary glioblastoma.